Dynamics of microbial communities in Western Antarctic Peninsula waters shaped primarily by the biological interactions - Pavlovska, Mariia; Zotov, Andrii; Prekrasna-Kviatkovska, Yevheniia; Sidhu, Chandni; Dzhulai, Artem; Dzyndra, Marta; Dykyi, Evgen (Frontiers in Microbiology, 2025)
Marine Antarctic microbial communities inhabit highly dynamic and extreme environments, characterized by deep vertical mixing, seasonal ice cover, and fluctuating light availability. Understanding the interplay between phytoplankton and bacterioplankton in such systems is critical to elucidate ecosystem function and biogeochemical cycling in the Southern Ocean. The current study presents a comprehensive three-year high-throughput analysis of phytoplankton-bacterioplankton interactions in the waters of Wilhelm Archipelago, elucidating interseasonal and interannual microbial dynamics. The results showed distinct dynamic patterns of microbial taxonomic structure and functional repertoire with heterotrophic phytoplankton-associated bacteria (e.g., Polaribacter, Yoonia, Sulfitobacter, Amylibacter, and gammaproteobacterial clade SAR92) dominating in spring and summer, and oligotrophic and chemolithoautotrophic taxa (Polaromonas and Paraglaciecola) prevailing in autumn. Positive correlations were detected between Bacillariophyceae, Coccolithophyceae, and Dinophyceaea with Sulfitobacter and Yoonia, emphasizing their association with phytoplankton abundance. Indirect functional predictions using the PICRUSt2 pipeline demonstrated seasonal shifts in bacterioplankton metabolic potential. Bacterial genes encoding carbohydrate degradation and sulfatases, crucial for algal sulfated polysaccharide breakdown, were most abundant during phytoplankton development, while DMSP demethylation genes peaked in summers of 2019 and 2020, following ice retreat and mass-development of Phaeocystis antarctica (Coccolithophyceae). Additionally, elevated uric acid degradation genes suggest an ornithogenic influence from the expanding penguin colony on nitrogen cycling within the marine ecosystem. These findings highlight the pivotal role of seasonal phytoplankton dynamics in structuring bacterioplankton communities and provide novel insights into microbial-mediated biogeochemical processes in the Southern Ocean.